Structure-activity relationships among mono- and dihydroxy flavones as aryl hydrocarbon receptor (AhR) agonists or antagonists in CACO2 cells. (25th September 2022) - Park, Hyejin; Jin, Un-Ho; Martin, Gregory; Chapkin, Robert S.; Davidson, Laurie A.; Lee, Kyongbum; Jayaraman, Arul; Safe, Stephen
Abstract: Unsubstituted flavone induced CYP1A1, CYP1B1 and UGT1A1 gene expression in Caco2 cells and was characterized as an aryl hydrocarbon receptor (AhR) agonist. The structure-activity relationships among 15 mono- and dihydroxyflavones showed that addition of one or two hydroxyl groups resulted in active (e.g.: 5- and 6- mono- and 5, 6-dihydroxyflavones) and inactive (e.g.: 7-mono, 7, 4′ and 6, 4′-dihydroxyflavones) AhR ligands. Ligand docking studies of flavone, mono- and dihydroxyflavones to the human AhR resulted in similar docking scores that varied from −3.48 to −4.58 kcal/mol and these values did not distinguish between AhR-active and AhR-inactive mono- and dihydroxyflavones. The AhR-inactive flavones were subsequently investigated as AhR antagonists by determining their activities as inhibitors of TCDD-induced expression of CYP1A1, CYP1AA2 and UGT 1A1 gene expression in Caco2 cells. Initial studies with 7, 4′-dihydroxyflavone showed that this compound was an AhR antagonist in Caco2 cells and resembled the activity of the classical AhR antagonist CH223191. With few exceptions most of the remaining AhR-inactive compounds in terms of inducing AhR responsive genes were also AhR antagonists. Thus, based on modeling studies, mono- and dihydroxyflavones bind with similar affinities to the AhR and exhibit AhR agonist or antagonist activities, however, the structural requirements (substitution patterns) for predicting these opposing activities were not apparent and could only be determined using bioassays. Highlights: Flavone activates the aryl hydrocarbon receptor (AhR). Lower hychoxyflavones also activate the AhR. Some hychoxyflavones are AhR antagonists. SARs for AhR agonist/antagonist activities not apparent.